2017
DOI: 10.1111/gcb.13985
|View full text |Cite
|
Sign up to set email alerts
|

Rock glaciers in crystalline catchments: Hidden permafrost‐related threats to alpine headwater lakes

Abstract: A global warming‐induced transition from glacial to periglacial processes has been identified in mountainous regions around the world. Degrading permafrost in pristine periglacial environments can produce acid rock drainage (ARD) and cause severe ecological damage in areas underlain by sulfide‐bearing bedrock. Limnological and paleolimnological approaches were used to assess and compare ARDs generated by rock glaciers, a typical landform of the mountain permafrost domain, and their effects on alpine headwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 111 publications
(140 reference statements)
0
45
0
Order By: Relevance
“…This is in line with the literature on rock glacier hydrology stating that these landforms act as unconfined aquifers in mountain slopes (e.g., Jones et al, ; Krainer & Mostler, ). The enrichment of solutes and trace elements in rock glacier outflows is commonly attributed to the thaw of internal ice and to the associated weathering of freshly exposed rock particles (Colombo et al, ; Ilyashuk, Ilyashuk, Psenner, Tessadri, & Koinig, ; Munroe, ; Williams, Knauf, Caine, Liu, & Verplanck, ). Accordingly, the high values of EC, major ions, and trace elements, we observed increasing over the season, are consistent with data reported in the literature on rock glacier hydrology (e.g., Colombo et al, ; Mair et al, ; Millar, Westfall, & Delany, ; Williams et al, ) and suggest that part of the rock glacial baseflow in summer came from permafrost thaw, in addition to the groundwater fraction, and this increased as summer progressed.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the literature on rock glacier hydrology stating that these landforms act as unconfined aquifers in mountain slopes (e.g., Jones et al, ; Krainer & Mostler, ). The enrichment of solutes and trace elements in rock glacier outflows is commonly attributed to the thaw of internal ice and to the associated weathering of freshly exposed rock particles (Colombo et al, ; Ilyashuk, Ilyashuk, Psenner, Tessadri, & Koinig, ; Munroe, ; Williams, Knauf, Caine, Liu, & Verplanck, ). Accordingly, the high values of EC, major ions, and trace elements, we observed increasing over the season, are consistent with data reported in the literature on rock glacier hydrology (e.g., Colombo et al, ; Mair et al, ; Millar, Westfall, & Delany, ; Williams et al, ) and suggest that part of the rock glacial baseflow in summer came from permafrost thaw, in addition to the groundwater fraction, and this increased as summer progressed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a localised inflow from the RG has been confirmed [17], but it is important to specify that these meltwater inputs have been described as intermittent, concentrated only in the snow-free season and mainly linked to precipitation events [17,20]. Meltwaters also showed only a moderate increase in solutes concentration if compared with the pond waters [20], differing in this sense from other RGlake/stream systems affected by natural acid rock drainage phenomena [9,14,15]. Nevertheless, beside RG inputs can be limited in frequency and magnitude, microbial communities can quickly react to environmental pressures acting directly or indirectly on them [21], becoming a powerful instrument for the detection of ecosystem perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Thies et al [9] compared the diatom population of RG-influenced and reference streams in the Austrian Alps, highlighting that both diatom species composition and diversity can be negatively affected by the increase in water acidity commonly associated with RG runoff. In the NE Italian Alps, Ilyashuk et al [14,15] reported high concentrations of metals in the waters of RG lakes, which seem to explain the high rate of morphological abnormalities in chironomid population inhabiting lake sediments. Focusing on microbial community, Fegel et al [8] described the bacterial community composition in stream sediments collected close to the terminus of several glaciers and RGs, distributed across three North America mountain ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Being potentially unstable slopes and solid water reservoirs, rock glaciers and their dynamics have gained importance in climate change research in recent decades . Higher mean annual temperatures are expected to induce changes to surface and subsurface dynamics at different temporal scales (e.g., weekly to decadal), depending on site‐specific conditions …”
Section: Introductionmentioning
confidence: 99%
“…6 Higher mean annual temperatures are expected to induce changes to surface and subsurface dynamics at different temporal scales (e.g., weekly to decadal), depending on sitespecific conditions. [6][7][8][9][10][11][12][13] These surface and subsurface dynamics reflect processes of rock glacier deformation including permafrost creep, permafrost slide, zonal thinning or thickening, advection of surface microtopography, three-dimensional (3D) straining, general mass changes (heaving or settlement), and horizontal shearing and rotation. 14 These processes feature different spatial characteristics, magnitudes and timescales of occurrence.…”
Section: Introductionmentioning
confidence: 99%